Rivalidad femenina en Meleagro de Eurípides - Perczyk, Cecilia J.; Maresca, Victoria (Lexis)
In Euripides’ tragedy, Meleager murders his maternal uncles in order to offer the boar’s offal from Calydon to Atalanta. In response to the deaths of his brothers, Althea decides to throw the brand, which holds her son’s life, into the fire. We hypothesise that the introduction of Meleager’s love for Atalanta in the tragedy structures the plot around the two women’s rivalry. We will study a selection of fragments to understand the fact that a woman makes an attempt on her own child’s life, considering that procreation is the central purpose of women in classical Athens.